Моделювання та дослідження магнітоелектричного перетворювача для гідро- та пневмоприводів - Римша, В. В.; Радимов, І. М.; Гулий, М. В.; Бабич, І. П.; Калиниченко, О. А.; Деменко, Микола Петрович (Національний технічний університет "Харківський політехнічний інститут", 2023)
Наведено результати моделювання та практичної реалізації магнітоелектричного перетворювача для гідро- та пневмо-приводів аерокосмічної галузі. На основі серії проектних розрахунків при різноманітній конфігурації магнітної системи перетворювача обрано варіант з чотирма зубцями на полюсі статору і отримані його основні характеристики. Результати розрахунків зіставлені з результатами експерименту на макетному зразку магнітоелектричного перетворювача.

Presentation of the results of modeling and practical implementation of a magnetoelectric converter for hydraulics and pneumatics systems of the aerospace industry. Methodology. Calculations of three-dimensional magnetic fields are carried out with the Finite Element Method by JMAG program. The solution of the differential equations connecting the input voltage, current, magnetic flux and torque is performed by numerical integration. Results. As a result of calculations, the converter configuration was obtained. Tests of the prototype model of the converter confirmed the principle workability of the adopted design and design solutions in its development. Practical value. Tests of the converter prototype sample confirmed the fundamental performance of the adopted design and constructive solutions.
Modeling and research of a magnetoelectric converter for hydro and pneumo actuators
Keywords: магнітоелектричний перетворювач; тривимірне магнітне поле; механічні характеристики; макетний зразок; magnetoelectric converter; three-dimensional magnetic field; mechanical characteristic; prototype sample